CHANGES IN THE MORPHOLOGICAL AND MORPHOMETRIC PARAMETERS OF THE GASTRIC WALL IN POLYPRAGMASS WITH ANTI-INFLAMMATORY DRUGS - Toshmamatov Bakhtiyor Norbekovich; Djumanova Nargiza Eshmamatovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
In the contemporary world, there is a rapid increase in the invention and application of a large number of medications (drugs) in practical health care, which, on the one hand, can cure and/or enhance the patient's condition, but also do substantial harm to his health. The purpose of this study was to add to the body of knowledge on polypragmas that develop following nonsteroidal therapy in rats. Gastric tissue was morphologically examined in 55 rats to attain the aim. The findings revealed that nonsteroidal therapy resulted in an increase in the amount of mucous membranes and lymphoid follicles, proliferation of vascular wall cells, and poor stratification of connective tissue cells in the stomach.